A Multilevel Inverter Based on SVPWM Technique for Photovoltaic Application. - Shantanu Chatterjee (International Journal of Power Electronics and Drive Systems (IJPEDS), 2013)
Multilevel inverters can reach the increasing demand for power quality and power ratings along with lower harmonic distortion and lesser electromagnetic interference (EMI). As the number of levels increases, it is important to control more switches in parallel with their concurrent processing capability. In this paper space vector pulse width modulation (SVPWM) Technique is proposed for the two-level and three-level neutral point clamped (NPC) inverter. Due to the geometrical symmetry of six sectors, there will be close relationship between on-time arrangements and on-time calculations for switches respectively. The two and three level inverter is simulated using MATLAB/Simulink and also the experimental results are presented for verifying the effectiveness of the system. The use of Photovoltaic Cell as source for the NPC Inverter is proposed here in this paper.DOI: http://dx.doi.org/10.11591/ijpeds.v2i4.403